Pertimbangan Hakim dalam Putusan Perceraian yang Mengandung Unsur Tindak Pidana (Study Putusan No. 152/Pdt.G/2018/Pn.Dps) - I Putu Bayu Permana; Anak Agung Sagung Laksmi Dewi; Diah Gayatri Sudibya (Jurnal Analogi Hukum, 2020)
Abstract—The problem in this study is how the judges' consideration in the divorce decision contains elements of crime No. 152 / Pdt. G / 20018 / Pn.Dps. where in developing countries Indonesia is very vulnerable to divorce. This is due to the fact that there are movie players or celebrities who divorce and remarry. In the making of the film also did the scene of remarrying without the knowledge of the first wife, which according to the author caused the divorce to be susceptible to an element of crime. Law No. 1 of 1974 concerning marriage has detailed explained the importance of marriage and the requirement to remarry, the formulation of the problem raised is how is the regulation of divorce containing criminal elements? And judges' consideration in deciding divorce cases that has elements of criminal offense? the issues that will be discussed later will be reviewed based on a normative point of view, the laws and regulations of Denpasar court No. 152 / Pdt. G / 20018 / Pn.Dps. Consider this judge in the decision no. 152 / Pdt. G / 20018 / Pn.Dps, considering that the plaintiff committed a criminal offense under article 279 KHUPidana, that it was the plaintiff who first made the attack arising from remarriage without the knowledge of the first wife, based on the Supreme Court jurisprudence No. 2571 k / Pdt / 1988 husbands or wives or parties that cause disputes and disputes, are not entitled or unable to act as plaintiffs. In the plaintiff's claim, the judge stated that the claim could not be accepted, and paid all court fees in the trial.